Nilai-Nilai Pancasila Sebagai Pedoman Dalam Menepis Kejahatan Terorisme - Novita Anggraeni; Rachel Cantika Redias Pradita; Risma Wahyu Giyantari; Riska Andi Fitriono (Gema Keadilan, 2022)
Terrorism is one of the serious threats to the sovereignty of every country because it has posed a danger to the security of world peace and harmed the welfare of the people. This article intends to study the values of Pancasila as a guide in dismissing the crime of terrorism in Indonesia and formulate its application in people's lives. The research method used in writing this article is to use a literature study approach, namely journals, books, and a number of related articles. This paper aims to find out the factors that cause terrorism, the role of Pancasila in overcoming cases of terrorism in Indonesia, and how to prevent the influence of terrorism crime.